Strong-Field Chiral Light-Matter Interaction - Bégin, Jean-Luc (Université d'Ottawa / University of Ottawa, 2024)
The physical world is asymmetric in nature. This broken symmetry manifests itself throughout the micro and macro worlds, ranging from fundamental particles to the realm of molecules, and from biological organisms to spiral galaxies. Therefore, chirality is of interest to physicists, chemists, and biologists alike. The study of chiroptical phenomena requires an interaction between two chiral systems - a chiral reagent with known handedness that can induce a differential response of non-superimposable chiral objects. Chiroptical effects are conventionally performed using Circularly polarized light (CPL) as their chiral probe. This dissertation presents a conceptually new form of chiroptical detection technique using the helical phase of light as the chiral probe. Structured light beams, also known as helical light beams, can carry Orbital Angular Momentum (OAM) ±𝑙ℏ which is associated with the dynamical rotation of wavefront structure. The intensity profile of such light is characterized by a phase singularity (optical vortex) and hence a null intensity region at the center of the beam. The handedness of these beams is associated with the twisting of the wavefront undergoing 𝑙 intertwined rotations in one wavelength. This is analogous to the chiral structure of the electric field associated with CPL. Moreover, helical light can be categorized as symmetrical and asymmetrical OAM beams. The latter is achieved by displacing the phase singularity, resulting in an additional degree of control over these structured beams. Therefore, by using asymmetrical helical light as a chiral probe, two extra degrees of freedom are gained to study chiral interactions. i) The theoretical unbounded 𝑙-value, which increases the number of intertwined twists within the helical pitch which in principle could increase the chiral sensitivity with the 𝑙-value. ii) The asymmetrical parameter δ, affects the field strength and the field gradient around the optical vortex. We show that these additional degrees of freedom can influence and control the sensitivity of the chiral signal. The chiral response from the helical light can be classified by two types of Helical Dichroism (HD) signals: HD(Type I) defined as the differential absorption of left- and right-helical light for a specific molecule and HD(Type II) defined as differential absorption between the two chiral objects for a specific helicity and polarization of light. Our observations demonstrate that HD(Type I) is a beam-dominant property where the broken symmetry of the helical light can induce a differential response in randomly orientated molecules or solids with or without structural symmetry. While, HD(Type II) is a material property and is sensitive to both chiral molecular and crystalline structures. Using absorption spectroscopy, we demonstrated the first direct observation of HD in liquid, solid, and gas phases using linearly polarized asymmetrical helical light as the chiral probe without the use of any intermediary. (i) We show that enantio-pure liquids exhibit enantio-selectivity, a phase effect that can be enhanced by the 𝑙-value and controlled by the asymmetrical parameter δ. Contrary to conventional beliefs, we found that HD(Type I) occurs even in randomly orientated achiral liquids. These discoveries highlight the benefits of using asymmetrical helical light as the chiral probe and shift the paradigm of chiroptical detection from laser polarization to the optical helical phase. (ii) To further solidify the significance of HD as a chiroptical technique, we demonstrated its presence in enantiomeric solutions with varying concentrations, since solvents can alter the structure and properties of biomolecules thereby modifying their function and reactivity. These chiroptical effects are not exclusive to molecular structures; they can also occur in crystalline structures. In solid-state materials, the higher density combined with the inherent birefringence and macroscopic anisotropies often mask the optical signal of traditional methods. (i) We demonstrate that helical light can map crystal symmetry, and differentiate chiral crystals with an HD signal one to two orders of magnitude higher than when using CPL. We also show that achiral crystals exhibit HD(Type I) and the magnitude of the signal is influenced by the bandgap. These results demonstrate that the crystal structure in solid-state matter responds strongly to the optical helical phase compared to CPL. (ii) This novel form of solid-state optical dichroism is not limited to crystalline structures. We observe the first existence of intrinsic dichroism in amorphous solids using asymmetrical helical light beams. Such an effect is typically unexpected in glass materials due to the disorderly state of the medium. Suggesting that HD(Type I) is responsive to the short-range order of amorphous materials. This new development in chiroptical techniques can aid the understanding of the mysterious nature of amorphous materials and the development of various optical applications. In the gas phase, two techniques are introduced to study chiral systems. Both implement a time-of-flight mass spectrometer (TOFMS) detection scheme; however, we use two different chiral probes. (i) Elliptical dichroism using a femtosecond laser mass spectrometer provides a molecular fingerprint of the interaction by measuring the ions and fragments produced during the ionization and recollision process. The chiral recollision yields are influenced by the handedness of the elliptically polarized light. This method overcomes the limitation of needing pure enantiomers or prior chemical separation for measurements. The chiral efficiency is significantly higher than conventional Circular Dichroism (CD) and comparable to Photoelectron circular dichroism (PECD). (ii) Orbital angular momentum-dependent strong-field ionization reveals that asymmetrical helical light offers new dimensions to control the strong-field ionization of atoms and molecules. Our findings indicate that the ions and fragments of chiral and achiral molecules are strongly influenced by the handedness, the 𝑙-value of the OAM, and can be manipulated by shifting the phase singularity. This allows us to examine the effect of helical light on any element of the molecular composition. Moreover, this differential ionization is not limited to molecules; we show that argon exhibits similar ionization effects. In a vacuum system, the absence of significant intermolecular interactions and propagation leads to a clean chiroptical signal with high sensitivity compared to the liquid and solid phases. Also, by using asymmetrical helical light the field strength and the field gradient around the optical vortex can be manipulated which can increase the ponderomotive energy and acceleration compared to Gaussian light, and this effect intensifies with an increase in the 𝑙-value. These discoveries offer new opportunities in strong-field and plasma physics, potentially creating applications of asymmetrical helical beams in all states of matter. In the liquid phase, we model light-matter interaction by considering multipole expansion in the perturbative regime. We find that HD arises from the coupling of the electric dipole and electric quadrupole terms. In the solid phase, we model HD by considering electron transitions via Multiphoton-Assisted Tunneling (MPAT). This process ensures that electron displacement remains within the short-range order in solids, enabling us to effectively probe intrinsic dichroism. In the gas phase, we extend the model to the non-perturbative tunneling regime and demonstrate that the differential ionization results from the field strength and gradient directly influencing the molecular and atomic potential. The advantages of using asymmetrical helical phased light as a chiral reagent in all three phases of matter include the ability to tune and precisely control the amplitude of HD(Type I). This can be achieved by (i) shifting the phase singularity in the beam, (ii) superposition of OAM and Gaussian beams, (iii) varying the l-value, and (iv) varying the laser polarization. These unique characteristics, along with the bandgap and ionization potential dependence of HD and differential ionization, distinguish this technique from other existing polarization-based chiroptical methods.
Keywords: Strong-field physics; Chirality; Chiroptical techniques; Helical dichroism; Circular dichroism; Nonlinear multiphoton absorption; Tunnel ionization